(untitled) (The São Paulo Journal of Mathematical Sciences, 2010)
We show how the matrix problems can be used in studying triangulated categories. Then we apply the general technique to the classi cation of stable homotopy types of polyhedra, and out the epresentation types" of such problems and give a description of stable homotopy types in nite and tame cases.